Nucleotide Sequence Requirements at the 5′ End of the Influenza A Virus M RNA Segment for Efficient Virus Replication - Ozawa, Makoto (American Society for Microbiology (ASM), 2009)
The mechanism by which the influenza A virus genome is packaged into virions is not fully understood. The coding and noncoding regions necessary for packaging of the viral RNA segments, except for the M segment, have been identified. Here, we delineate the M segment regions by incorporating a reporter viral RNA into virions and by generating viruses possessing mutations in the regions. We found that, like the other segments, the M segment coding regions are essential for virion incorporation and that the nucleotide length rather than the nucleotide sequence of the 5′ end of the coding region is important.